Genomic analysis of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) strains isolated in Malaysia - Hooi-Leng Ser; Loh Teng-Hern Tan; Jodi Woan-Fei Law; Vengadesh Letchumanan; Nurul-Syakima Ab Mutalib; Learn-Han Lee (Progress in Microbes and Molecular Biology)
Using seven complete genomes of human SARS-CoV-2 (retrieved from GISAID) isolated in Malaysia for phylogenetic tree construction, the current study showed that these strains formed four distinct clades when compared with other representative strains from Asia, Europe and US. In light of that, the genome sequences of these strains isolated in Malaysia suggested that there is currently more than one “type” of strain within the country. Complementing with epidemiological and experimental studies, these findings allow better understanding the prevalence of certain types in Malaysia and permits further in-depth studies on the virulence and pathogenic mechanisms of these strains which is particularly critical to speed up the development of effective treatment regime.